A simplified approach for the response of pile groups composed of dissimilar piles. (December 2021) - Liu, Shan-wei; Zhang, Qian-qing; Cui, Chun-yu; Feng, Ruo-feng; Cui, Wei
Abstract: In practice, saddle-shaped settlement is often investigated in the pile group foundation with identical piles. For the purpose of decreasing the differential settlement, uneven-distributed pile groups can be used. This paper provides a simplified approach to capture the behaviour of pile groups with dissimilar pile length or pile diameter. The hyperbolic function was adopted to express the mechanism of the interface between pile and soil. Considering the interaction of piles with dissimilar length, the hyperbolic load-transfer model of individual pile in pile groups composed of dissimilar piles were proposed. The related parameters of load transfer function of pile shaft or pile base of dissimilar piles were determined. To clarify the deformation mechanism of pile-soil system, an iterative approach for the analysis on the behaviour of non-uniformly arranged pile groups was proposed. Comparisons between the present computation results and the finite element simulation results were drawn to check the dependability of the proposed approach. Moreover, taking 3 × 3 pile groups as an example, the bearing characteristics of the centre pile, the edge pile and the corner pile in pile groups with different pile arrangements were analysed. For practical purposes, some suggestions on the pile groups composed of dissimilar piles were given to alleviate differential settlement among each individual pile and decrease the cost of pile groups and the construction difficulties.